Interactions of the local governance and the citizens on Facebook: the case of Lithuanian municipalities - Aurylaitė, Ieva (Information & Media, 2017)
Due to the process of globalization, it is possible to notice the increase of influence caused by the political power decentralization process on the political communication of local governance and citizens. Political decentralization is a process in the course of which the members of territorial communities and their elected representatives acquire more power in making public decisions. The citizens of the local governance are not involved in the political decision-making process; therefore, the problem of democratic deficit is increasing. The aim of the article is to reveal the communication specifics of local governances (municipalities) and citizens in social media. The influents of the decentralization process of political power at the local governance level are important to identify in the Lithuanian information society. By revealing the influence of the political power decentralization process at the local governance level, emphasized is the importance of accountability and responsiveness in forming the Lithuanian information society. Scientific researches concerning procedural dimensions of liberal democracy, such as accountability and responsiveness, help to reveal the possibilities of interest representation in the course of political decision-making in the digital public sphere. In the article represented is a quantitative content analysis about the information disclosure strategies of Lithuanian municipalities and citizens on the social network Facebook conducted in 2015–2016. The research evaluated interaction – the relation of disclosed and used information, helping to reveal optimal information disclosure strategies on Facebook. In making an assessment of electronic participation strategy, most attention is given to the accountability and responsivity criteria, as it helps to keep up the principle of subsidiarity. The specific character of new media logic is notable in mutual communication and operational efficiency of information disclosure; however, information announced by a political institution (municipality) is rather familiar and oriented toward one-way communication. Local governance initiates citizens to partake in the political decision-making process only when information is organized on Facebook.